Adjustment Problems dan Psychological Well-Being pada Siswa Akseleran (Studi Korelasional pada SMPN 19 Jakarta dan SMP Labschool Kebayoran Baru) - Misero, Priscillia Susan; Hawadi, Lydia Freyani (Jurnal Psikologi: PITUTUR, 2012)
Owned by a gifted student akseleran, as intellectually gifted students,taking  them  to  the  demands  of  external  and  internal  demands.  A  student akseleran must adapt themselves to these demands. However, it is not easy.There are a number of problems they face because of it. Noted there are six main problems of adjustment (adjustment problems) students akseleran ie, school  assignments  are  not  challenging,  poor  interpersonal  relationships, parental expectations,  perfectionism,  multipotensialitas,  and  high involvement  (Chan,  2006).  Those  problems  are  a  source  of  stress  for students  and  psychological  conditions  may  interfere  with  his  well-being.This  is  certainly  not  beneficial  because  it  can  cause  the student  can  not perform optimally. This study seeks to prove whether there is a relationship between  adjustment  problems  and  psychological  well-being  in  students akseleran  ..  In  addition,  this  study  also  attempted  to  figure  out  what adjustment  the  most  significant  problems  associated  with  psychological well-being.Melalui  a  correlational  study  in  SMP  and  SMP  19  Jakarta Labschool  Kebayoran  Baru,  found  a  significant  negative  relationshipbetween  psychological  adjustment  problems  with  the  well-being  thestudents  akseleran.  In  addition,  problems  of  adjustment  dimensionsperfectionism  is  a  problem  that  has  the  most  significant  relationship  with psychological well-being.